The impact of physical activity on working memory in children with ADHD: a meta-analysis - Cheng, Gong; Song, Ce; Hong, XiaoQin (Frontiers in Psychiatry, 2025)
BackgroundAttention-Deficit/Hyperactivity Disorder (ADHD) is a common neurodevelopmental disorder in children, often associated with impairments in working memory and other cognitive functions. Physical activity interventions have gained attention as a promising non-pharmacological strategy to alleviate these deficits. The present study aims to systematically evaluate the effects of physical activity on working memory in children with ADHD through meta-analysis, examining its potential mechanisms and providing evidence-based recommendations for comprehensive interventions.MethodsThis systematic review and meta-analysis followed the PRISMA guidelines. PROSPERO registration number CRD420250653800. We included controlled trials involving children clinically diagnosed with ADHD that examined the effects of physical activity interventions on working memory or cognitive functions. Literature was systematically searched in PubMed, Web of Science, Cochrane Library, Embase and CNKI from inception to January 2025. Two independent reviewers screened studies, extracted data, and assessed methodological quality using the Cochrane Risk of Bias Tool. Standardized mean differences were calculated using a random-effects model. Subgroup analyses were conducted by intervention characteristics such as duration, frequency and total time. Sensitivity analyses and publication bias assessment using funnel plots and Egger test were used to evaluate the robustness of the findings.ResultsA total of 11 studies involving 667 participants were included. The meta-analysis showed that physical activity interventions significantly improved working memory in children with ADHD, with a moderate effect size (SMD = 0.51, 95% CI: 0.34 to 0.69). Subgroup analyses indicated that interventions with moderate duration and frequency (45–60 minutes per session, 8–12 weeks, ≤2 times per week, and ≤25 total hours) were associated with the most stable and effective outcomes.ConclusionPhysical activity interventions are effective in improving working memory in children with ADHD, especially when implemented with optimal session duration, frequency, and total intervention time. These findings support the inclusion of structured physical activity programs in clinical and educational settings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420250653800.